O estatuto variável de construções com e sem alçamento: Uma abordagem sociofuncionalista - Gonçalves, Sebastião Carlos Leite [UNESP] (FapUNIFESP (SciELO), 2017)
Argument constituent of embedded clause can take typical behavior of Subject or Object in a matrix predication, phenomenon named as Raising. Under socio-functionalist approach, we discuss the variable status of constructions with and without raising, assuming the hypothesis that such constructions can be considered as variants of the same syntactic variable. Regardless of prototypical morphosyntactic adjustments of raising, we analyzed data from a spoken Brazilian Portuguese variety involving Raising to Subject constructions. Considering both linguistic and social variables, the results indicate, in the conditioning of variable rule: (i) Subject to Subject Raising is more productive than Object to Subject Raising; (ii) semantic-pragmatic variables are more relevant; (iii) social variables are irrelevant. The conclusion is that a satisfactory treatment of the phenomenon under socio-functionalist perspective it requires that morphosyntactic criteria are mitigated in favor of the inclusion of discursive-pragmatic criteria.
The variable status of constructions with and without raising: A socio-functionalist approach
Keywords: Brazilian Portuguese; Raising; Socio-functionalism; Syntactic variation